HIGHER-ORDER THINKING SKILLS (HOTS) ANALYSIS OF STUDENTS IN SOLVING HOTS QUESTION IN HIGHER EDUCATION - Siti Rohmi Yuliati; Ika Lestari (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2018)
Students of Elementary School Teacher Education programs must be able to have higher-order thinking skills (HOTS) so that they can train students to have HOTS through learning activities created when they have become elementary school teachers. This study aims to explain students' high-level thinking skills in solving HOTS-oriented questions in Instructional Evaluation courses. This study uses qualitative research methods with data collection techniques using cognitive test instruments in the form of descriptions. Data analysis techniques use simple descriptive statistics. The results showed the level of thinking ability of students in answering HOTS practice questions still needed improvement. Students who have high learning abilities are better at answering HOTS-oriented questions compared to students in the medium and low categories. Recommendations for future research are required learning modules that can facilitate learning activities that lead to HOTS so that students are skilled in answering and making HOTS-oriented practice questions for elementary school students when they become a teacher. References Abdullah, Abdul Halim; Mokhtar, Mahani; Halim, Noor Dayana Abd; Ali, Dayana Farzeeha; Tahir, Lokman Mohd; Kohar, U. H. A. (2017). Mathematics Teachers’ Level of Knowledge and Practice on the Implementation of Higher-Order Thinking Skills (HOTS). EURASIA Journal of Mathematics, Science and Technology Education, 13(1), 3–17. https://doi.org/10.12973/eurasia.2017.00601a Altun, M., & Akkaya, R. (2014). Mathematics teachers’ comments on PISA math questions and our country’s students’ low achievement levels. Hacettepe Üniversitesi Eğitim Fakültesi Dergisi, 29(1), 19–34. Bakry, & Md Nor Bakar. (2015). The process of thinking among Junior High School students in solving HOTS question. International Journal of Evaluation and Research in Education (IJERE), 4(3), 138–145. Budsankom, P; Sawangboon, T; Damrongpanit, S; Chuensirimongkol, J. (2015). Factors affecting higher order thinking skills of students: A meta-analytic structural equation modeling study. Educational Research and Review, 10(19), 2639–2652. doi:10.5897/err2015.2371 Chinedu, C. C., Olabiyi, O. S., & Kamin, Y. Bin. (2015). Strategies for improving higher order thinking skills in teaching and learning of design and technology education. Journal of Technical Educationand Training, 7(2), 35–43. Retrieved from http://penerbit.uthm.edu.my/ojs/index.php/JTET/article/view/1081/795 Didis, M. G., Erbas, A. K., Cetinkaya, B., Cakiroglu, E., & Alacaci, C. (2016). Exploring prospective secondary mathematics teachers’ interpretation of student thinking through analysing students’work in modelling. Mathematics Education Research Journal, 28(3), 349–378. https://doi.org/10.1007/s13394-016-0170-6 Duan, J. (2012). Research about Technology Enhanced Higher-Order Thinking. IEEE Computer Society, (Iccse), 687–689. https://doi.org/10.1109/ICCSE.2012.6295167 Edwards, L. (2016). EDUCATION, TECHNOLOGY AND HIGHER ORDER THINKING SKILLS Lucy Edwards, 1–18. Ersoy, E., & Başer, N. (2014). The Effects of Problem-based Learning Method in Higher Education on Creative Thinking. Procedia - Social and Behavioral Sciences, 116, 3494–3498. https://doi.org/10.1016/j.sbspro.2014.01.790 Hugerat, M., & Kortam, N. (2014). Improving higher order thinking skills among freshmen by teaching science through inquiry. Eurasia Journal of Mathematics, Science and Technology Education, 10(5), 447–454. https://doi.org/10.12973/eurasia.2014.1107a Kaur, C., Singh, S., Kaur, R., Singh, A., & Singh, T. S. M. (2018). Developing a Higher Order Thinking Skills Module for Weak ESL Learners, 11(7), 86–100. https://doi.org/10.5539/elt.v11n7p86 King, F. J., Goodson, L., & Rohani, F. (1998). Higher order thinking skills. Publication of the Educational Services Program, Now Known as the Center for Advancement of Learning and Assessment. Obtido de: Www.Cala.Fsu.Edu, 1–176. Retrieved from http://www.cala.fsu.edu/files/higher_order_thinking_skills.pdf Kusuma, M. D., Rosidin, U., Abdurrahman, A., & Suyatna, A. (2017). The Development of Higher Order Thinking Skill (Hots) Instrument Assessment In Physics Study. IOSR Journal of Research & Method in Education (IOSRJRME), 07(01), 26–32. https://doi.org/10.9790/7388-0701052632 Marzano, R. J. (1993). How classroom teachers approach the teaching of thinking. Theory Into Practice, 32(3), 154–160. https://doi.org/10.1080/00405849309543591 McLoughlin, D., & Mynard, J. (2009). An analysis of higher order thinking in online discussions. Innovations in Education and Teaching International, 46(2), 147–160. https://doi.org/10.1080/14703290902843778 Miri, B., David, B. C., & Uri, Z. (2007). Purposely teaching for the promotion of higher-order thinking skills: A case of critical thinking. Research in Science Education, 37(4), 353–369. https://doi.org/10.1007/s11165-006-9029-2 Nagappan, R. (2001). Language teaching and the enhancement of higher-order thinking skills. Anthology Series-Seameo Regional Language Centre, (April 2000), 190–223. Retrieved from http://nsrajendran.tripod.com/Papers/RELC2000A.pdf Nguyen, T. (2018). Teachers ’ Capacity of Instruction for Developing Higher – Order Thinking Skills for Upper Secondary Students – A Case Study in Teaching Mathematics in Vietnam, 10(1), 8–19. Puchta, H. (2007). More than little parrots: Developing young learners’ speaking skills. Www.Herbertpuchta.Com. Raiyn, J., & Tilchin, O. (2015). Higher-Order Thinking Development through Adaptive Problem-based Learning. Journal of Education and Training Studies, 3(4), 93–100. https://doi.org/10.11114/jets.v3i4.769 Retnawati, H., Djidu, H., Kartianom, K., Apino, E., & Anazifa, R. D. (2018). Teachers’ knowledge about higher-order thinking skills and its learning strategy. Problem of Education in the 21st Century, 76(2), 215–230. Retrieved from http://oaji.net/articles/2017/457-1524597598.pdf Snyder, L. G., & Snyder, M. J. (2008). Teaching critical thinking and problem solving skills. The Delta Pi Epsilon Journal, L(2), 90–99. https://doi.org/10.1023/A:1009682924511 Stahnke, R., Schueler, S., & Roesken-Winter, B. (2016). Teachers’ perception, interpretation, and decision-making: a systematic review of empirical mathematics education research. ZDM - Mathematics Education, 48(1–2). https://doi.org/10.1007/s11858-016-0775-y Sulaiman, T., Muniyan, V., Madhvan, D., Hasan, R., & Rahim, S. S. A. (2017). Implementation of higher order thinking skills in teaching of science: A case study in Malaysia. International Research Journal of Education and Sciences (IRJES), 1(1), 2550–2158. Retrieved from http://www.masree.info/wp-content/uploads/2017/02/20170226-IRJES-VOL-1-ISSUE-1-ARTICLE-1.pdf Tan, S. Y., & Halili, S. H. (2015). Effective teaching of higher-order thinking (HOT) in education. The Online Journal of Distance Education and E-Learning, 3(2), 41–47. Thomas, A., & Thorne, G. (2009). How to increase higher level thinking | center for development and learning. The Center for Learning and Development Blog. Retrieved from http://www.cdl.org/articles/how-to-increase-high-order-thinking/ Thompson, T. (2008). Mathematics teachers’ interpretation of higher-order thinking in Bloom’s taxonomy. International Electronic Journal of Mathematics Education, 3(2), 96–109. https://doi.org/10.1126/science.318.5856.1534 Watson, J. M., Collis, K. F., Callingham, R. A., & Moritz, J. B. (1995). A model for assessing higher order thinking in statistics. Educational Research and Evaluation,(Vol.1). https://doi.org/10.1080/1380361950010303 Zohar, A. (2013). Challenges in wide scale implementation efforts to foster higher order thinking (HOT) in science education across a whole school system. Thinking Skills and Creativity, 10, 233–249. https://doi.org/10.1016/j.tsc.2013.06.002 Zohar, A., & Schwartzer, N. (2005). Assessing teachers’ pedagogical knowledge in the context of teaching higher-order thinking. International Journal of Science Education, 27(13), 1595–1620. https://doi.org/10.1080/09500690500186592 Zulkpli, Z., Mohamed, M., & Abdullah, A. H. (2017). Assessing mathematics teachers’ knowledge in teaching thinking skills. Sains Humanika, 9(1–4), 83–87. https://doi.org/10.11113/sh.v9n1-4.1129